Characterization of ash sludge from wastewater treatment plants: Assessment for construction purposes - Da Silveira Thiago Rosa, Cristiane Maria [UNESP]; Melges, José Luiz Pinheiro [UNESP]; Payá, Jordi [UNESP]; Akasaki, Jorge Luís; Marinho, Jean Richard Dasnoy [UNESP]; Oliveira, Douglas Santos [UNESP] (Trans Tech Publications, 2014)
Considering that the human being is in a universe where the population demand for consumer goods is rapidly growing, the United Nations (UN) concluded that the effective implementation of the use of renewable resources has a nearing deadline. As a result of population growth, a massive waste is generated, especially sewage, requiring adjustments in its disposal, treatment and final disposal. Based on this information, it must be highlighted that the generation of municipal waste due to the sewer, with a significant production of biogas and of sludge, presents major environmental problem due to their volume, size and features. This work points out that the ash of the wastewater sludge can have a more productive destination if used as an alternative material of construction. The research was divided into three stages. In the first stage, it was sample preparation sludge performed; in the second one, burning procedures were designed, and, in the third one, physical-chemical and mineralogical tests for the sewage sludge ash were made, seeking to assess the feasibility of using this residue in mortar and in concrete. According to the conducted studies, it was observed that there is a potential pozzolanic reactivity when using this material as a mineral admixture for Portland cement replacement.© (2014) Trans Tech Publications, Switzerland.
Keywords: Alternative material; Ash; Chemical property; Construction; Sewage sludge